U-Pb isotopy data of deformed samples from the Yushu mélange, western Jinsha Suture - Fanny Goussin; Stéphane Guillot; Gilles Ruffet; Marc Poujol; Émilien Oliot; Anne Replumaz; Carole Cordier; Guillaume Dupont-Nivet; Pierrick Roperch (PANGAEA, 2021)
Deformed samples from the Yushu mélange, in the western Jinsha Suture, have been dated by U-Pb isotopy on zircons. This dataset presents U-Pb isotopy data obtained for these samples. The rock sample was crushed using standard procedures. The zircon grains were handpicked from the 80-200 micrometer non-magnetic fraction, placed on epoxy mounts and polished. Back-scattered electron images of the grains were acquired with a Hitachi S2500 Scanning Electron Microprobe at the Institut des Sciences de la Terre (ISTerre) of Grenoble (France). U-Pb zircon analyses were performed by in-situ LA-ICP-MS, using an ESI NWR193UC excimer laser coupled to a quadrupole Agilent 7700x ICP-MS at the GeOHeLiS analytical Platform (OSUR, Univ. Rennes). The diameter of the ablation spots varies from 20 to 30 μm, depending on the grain size. The repetition rate of the ablation was 3 Hz. Data were corrected for U-Pb and Th-Pb fractionation and for mass bias by repeated measurements of the standard GJ-1 (Jackson et al., 2004). Accuracy was monitored by analyses of the standard Plešovice (337.13 ± 0.37 Ma, Sláma et al., 2008), which produced a concordia age of 337.1 ± 2.1 Ma (N=18; MSWD=0.65) during the course of the analyses. Data reduction was carried out using the software Iolite v4 (Paton et al., 2010, 2011). The concordia ages and diagrams were generated using IsoplotR (Vermeesch, 2018). The full instrumental and analytical conditions can be found in Table "Operating conditions for the LA-ICP-MS equipment" and in Nosenzo et al. (2022).